Comparison of internet addictions and its mental effects in medical and engineering students of a private university at Pune - Murarkar, Sujata K.; Sava, Shraddha N.; Gothankar, Jayashree S. (International Journal Of Community Medicine And Public Health, 2020)
Background: There has been explosive growth in the use of the internet. Internet addiction is upcoming problem and less researched entity. Study is conducted to compare internet addiction in engineering and medical students. Methods: A self-administered pretested predesigned questionnaire was used for data collection. Total 303 medical and engineering students were participated in the study. Young’s internet addiction test and DASS scale is used to measure internet addiction and psychological variables. Results: 23% were normal users, 59.1% were mild internet addicts, 17.4% were moderate internet addicts and 0.3% were severe internet addicts. There was strong positive relation between internet addiction and depression anxiety and stress. Conclusions: Internet addiction is a growing problem so it is important to create awareness among students to have a healthy lifestyle.